Verbal and physical violence in emergency departments: a survey of nurses in Istanbul, Turkey - (:unkn) unknown (WILEY-BLACKWELL PUBLISHING, INC, 2011)
Aims. The aim of this study was to determine the perceived verbal and physical violence and related factors experienced by nurses in emergency settings. Background. Studies on violence in emergency departments indicate an increasing frequency of these incidents. However, little is known about the violence experienced by the Turkish nurses working in emergency departments. Design. Survey. Methods. The study population included 255 nurses. Data were collected using a questionnaire. Results. Verbal violence was reported with a frequency of 91 center dot 4%. Of the nurses, 74 center dot 9% had been exposed to physical violence in at least several episodes during the previous 12 months. Patients' relatives were the main perpetrators, followed by patients, most of whom were male. After experiencing violence, most of the nurses reported that, they had felt fear and only 3% described that they took sick leave, while 80% did not report the incidences of violence they experienced. The nurses described that, after a violent incident, they sought support mainly from their colleagues in emergency departments rather than from the administration. Over half of the nurses (65%) felt safe 'none of the time' in emergency departments, and 89 center dot 8% of them described that patients and patient relatives may potentially exhibit violent behaviours towards the staff when they are first admitted to emergency department, while 73 center dot 7% believed that the staffing pattern and physical environment of their emergency departments were not adequate to prevent violence. Most of the nurses (83 center dot 5%) stated that they should be provided with the training that will help them prevent and manage violence as part of their in-service education, whereas 82 center dot 7% of them had not received any such training. Relevance to clinical practice. The findings have implications for occupational health and safety from both employer and employee perspective.
Keywords: emergency department; nurses; nursing; Turkey; violence; SETTINGS; WORKERS; ABUSE